A comparative and correlative study of serum homocysteine level in gestational diabetes mellitus and normal pregnancy - S., Manoharan; R., Sharmila; M., Natesh Prabhu (International Journal of Advances in Medicine, 2019)
Background: An alarming increase in Gestational diabetes mellitus (GDM) cases worldwide elevates concern regarding the consequences including fetal macrosomia, preeclampsia and many more. Plasma homocysteine levels which has direct impact on to endothelial function of blood vessels. The relationship of homocysteine and GDM is yet to be clarified. Methods: This single centre prospective observational study was conducted in Department of Obstetrics and Gynaecology of Thanjavur medical college hospital among 50 pregnant primi and multi gravida patients with normal pregnancy and gestational diabetes mellitus to assess the association and comparison of serum homocysteine levels in both groups. Results: The mean value of homocysteine in control group was 3.8 ± 0.95 and in gestational diabetes patients was 16.30±6.09. On comparison, found that there was hyperhomocysteinemia among GDM patients with normal pregnancy and results were statistically significant (T= -9.024 Df=48.000 <0.05). Conclusions: In this comparative and correlative study, we found that patients with gestational diabetes mellitus have higher serum homocysteine levels in comparison with normal pregnant women. Hyperhomocysteinemia is found to be an independent risk factor for gestational diabetes mellitus patients. Further investigations are needed to follow up for these patients in the postpartum period and later in their life.